Rice wastage of selected low income and high income families in Quezon City - Cabrera, Jonas Erik DL (College of Home Economics, University of the Philippines Diliman, 2016)
This study compared the rice wastage of selected low and high income families in Quezon City. It also determined the reasons for rice wastage, the methods that the families used to prevent rice wastage, and their practices in handling leftover rice. A total of twenty families were selected to participate in the study through purposive sampling. Half of the families belonged to the low income economic bracket while the other half belonged to the high income bracket. The study employed a researcher made interview guide to determine the families demographic information, their practices to prevent rice wastage, and their reasons for wasting rice. To measure rice wastage, each family was provided with a rice wastage bin wherein they threw the rice that they no longer intend to use. The weights of the collected rice were measured using a calibrated weighing scale. Results showed that high income families incur more rice wastage compared to low income families. Furthermore, the rice that the two groups disposed was generally still suitable for consumption. The reasons for rice wastage also differ between the two income groups. For low income families, the main reasons include the lack of proper storage for unconsumed rice and miscalculation of rice to be cooked. On the other hand, the reasons given by high income families include being innately wasteful and dining out. The common methods used by the families to prevent rice wastage include adding vinegar while cooking rice and proper estimation of rice. Finally, pagsasangag is the most observed practice in handling leftover rice for low income families while disposing is the most observed practice for high income families.